Using Commercial Bio-Functional Fungal Polysaccharides to Construct Emulsion Systems by Associating with SPI - Laixin Dai; Qingfu Wang; Lining Wang; Qinghua Huang; Biao Hu (Foods)
Fungi polysaccharides are nutraceutical-rich compounds with bioactive properties, offering promising applications in food formulation. This study examined the non-covalent complexation of commercial polysaccharides derived from the fruiting bodies of Auricularia auricula-judae (AA) and Ganoderma lucidum (GL) and soy protein isolate to enhance emulsifying properties. Complexes were examined across protein-to-polysaccharide ratios (0:1 to 1:0), pH levels (3 to 7), and heat treatment conditions. Results indicated a maximum insoluble association at pH 4 for both SPI-AAP and SPI-GLP complexes, with SPI-AAP complexes remaining soluble at pH 3, while SPI-GLP complexes exhibited insolubility. Heat treatment had a limited effect on electrostatically driven complexation but resulted in larger particles through a protein-denaturation-induced increase of hydrophobic interactions. In terms of emulsifying properties, individual GLPs demonstrated superior performance compared to individual AAPs. The GLPs engaged in competitive adsorption at the oil–water interface alongside SPI, resulting in larger emulsion droplet sizes compared to either component alone. The association of either AAPs or GLPs with SPI enhanced the emulsion stability against coalescence and Ostwald ripening. Commercial fungal polysaccharides demonstrate substantial potential for incorporation into manufactured food products, particularly in colloidal formulations.